Deep ecology and environmental sustainability: a study of Anuradha Roy's All the Lives We Never Lived - S, Arunya; Kumar, V. Vinod (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ecocriticism, as a separate school of literary criticism, emerged during the 1970s to study the interconnection between literature and ecology from an interdisciplinary perspective. Deep ecology is one of the key concepts in ecocritical studies, advocated by the Norwegian philosopher Arne Naess, that foregrounds the promotion of ecological consciousness among the human community. The deep ecological principles also highlight the depletion of natural resources through excessive human interference and exploitative attitudes. This paper attempts to critically examine the deep ecological principles in Anuradha Roy's novel All the Lives We Never Lived (2018). Anuradha Roy is an Indian novelist, editor, and journalist, and her novels gained significance not only in India but also in several countries, making her one of the prominent voices of contemporary Indian Literature. This paper explores the need for humans to realise the inherent values of the non-human world and to promote harmonious coexistence with the environment by valuing the richness and diversity of life forms and utilising them only to satisfy their vital needs. It further examines the need for a decrease in population for non-human life to flourish and to reduce excessive human interference with the ecosystem. This paper reiterates the necessity to adhere to each deep ecological principle, accentuating the significant, transformative changes to be embraced to promote environmental responsibility for sustainable living. These aspects are elucidated through relevant instances from the chosen novel.